Factors influencing outsourcing success in Malaysian automotive industry: The roles of degree of outsourcing and partner’s compatibility / Kashif Latif - Kashif , Latif (2019)
In the new age of innovation for developing and maintaining competitive advantage, organizations should focus on what is achievable in the market and utilize the innovations developed by other organizations. Fierce global competition, higher customer expectations, and continuously expanding supply chains have driven companies to outsource. Increasing globalization, technological advancements and increased customer expectations have created complex market structures and tightened competition in the marketplace. These factors have made the sustaining of organizations more challenging than ever. To ensure the success of outsourcing, the integration of tasks between focal and vendor organization must be well and efficiently managed. The purpose of this study is to identify the factors that need to be managed in the process of the integration of outsourcing tasks. In this thesis, exchange of resources is viewed from the perspective of the Social Exchange Theory. Vendor management capability, partnership quality, trust, human capital, knowledge sharing, degree of outsourcing and partners’ compatibility are identified as factors that have an impact on outsourcing success in manufacturing. This study also tests the effects of the magnitude of degree of outsourcing and partners’ compatibility in the collaborative business on outsourcing success. Cross-sectional data was collected through a survey of managers in the automotive industry of Malaysia using structured questionnaires. A total of 337 usable responses were collected. Structural Equation Modeling (SEM) was used to analyze the survey responses through smartPLS 3. The empirical analysis verified the nature of the influence of identified factors on outsourcing success. Degree of outsourcing explains the relationship between vendor management, partnership quality, trust and outsourcing success when outsourcing activities are moderate or extensive. This research contributes to the area of business strategy knowledge and expands the horizon of supply chain management from a strategic perspective. Specifically, the study highlights the importance of developing a balanced robust structured outsourcing system by using a balanced approach to degree of outsourcing where sustainable outsourcing success can be attained by value creation. Insights into this process are lacking in current literature. The factors recognized by this study provide guidelines for plan inputs and also for managing the process of manufacturing outsourcing. Managers in the automotive industry can use the model to evaluate the potential success of outsourcing. Additionally, they can evaluate the most suitable level of outsourcing and the expected compatibility of partners. This affords several strategic implications for practice. The analysis suggests that the degree of outsourcing mediates outsourcing success which gives clear indication as how much they have to outsource. It also suggests that partner compatibility has a direct impact on outsourcing success, and thus ultimately that managers should pay more attention to methods that augment the alignment of the vendor(s) and themselves. As a whole, this study highlights prominent factors which allow manufacturing industry stakeholders to plan, execute and assess outsourcing as a collaborative business practice that ensures mutual benefits as well as mutual success and survival.